ANALISIS KONSUMSI PANGAN RUMAH TANGGA PASCA KRISIS EKONOMI DI PROPINSI JAWA BARAT - ARIANI, MEWA; PURWANTINI, TRI BASTUTI (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 1 Februari 2006, 2012)
Food is the most fundamental need for household, directly related to the quality of human resources. The objective of this paper is to analyze the pattern of household food consumption in West Java province after economic crisis. Data are from SUSENAS year 1996,1999 and 2002. The results are : 1) Prosperity level of households after economic crisis is getting better, but it still lower than condition before crisis, 2) When the economic crisis happened, energy and protein consumptions of household decreased and the slope of it in West Java province was higher than national level. After economic crisis, consumption level of both nutrients then increase again, 3) Consumption of rice decrease after crisis, but consumption of instant noodle increase. The pattern of staple food consumption also change from rice pattern to rice-noodle pattern based of both region and income group. The implications of the policy is developing program of food diversification in the future must be implemented in more accurate way, supported by deeper research about consumer behavior. Besides, efforts to increase purchasing power and availability of some commodities such as animal foods, vegetables and fruits must be done. In accordance with that, people awareness of food, nutrition and health must be increase too. Political will and political power of governments are the success deciders.
Keywords: Food, Consumption, Household, Economic Crisis, West Java.